A High-resolution Spectroscopic Survey of Directly Imaged Companion Hosts. I. Determination of Diagnostic Stellar Abundances for Planet Formation and Composition - Aneesh Baburaj; Quinn M. Konopacky; Christopher A. Theissen; Sarah Peacock; Lori Huseby; Benjamin J. Fulton; Roman Gerasimov; Travis S. Barman; Kielan K. W. Hoch (The Astronomical Journal)
We present the first results of an extensive spectroscopic survey of directly imaged planet host stars. The goal of the survey is the measurement of stellar properties and abundances of 15 elements (including C, O, and S) in these stars. In this work, we present the analysis procedure and the results for an initial set of five host stars, including some very well-known systems. We obtain C/O ratios using a combination of spectral modeling and equivalent-width measurements for all five stars. Our analysis indicates solar C/O ratios for HR 8799 (0.59 ± 0.11), 51 Eri (0.54 ± 0.14), HD 984 (0.63 ± 0.14), and GJ 504 (0.54 ± 0.14). However, we find a supersolar C/O (0.81 ± 0.14) for HD 206893 through spectral modeling. The ratios obtained using the equivalent-width method agree with those obtained using spectral modeling but have higher uncertainties (∼0.3 dex). We also calculate the C/S and O/S ratios, which will help us to better constrain planet formation, especially once planetary sulfur abundances are measured using JWST. Finally, we find no evidence of highly elevated metallicities or abundances for any of our targets, suggesting that a super metal-rich environment is not a prerequisite for large, widely separated gas planet formation. The measurement of elemental abundances beyond carbon and oxygen also provides access to additional abundance ratios, such as Mg/Si, which could aid in further modeling of their giant companions.